Abstract ID: 182 Biophysical modelisation of gold nanoparticles radiosensitizing effects. (October 2017) - Poignant, Floriane; Gervais, B.; Ipatov, A.; Monini, C.; Cunha, M.; Lartaud, P.J.; Bacle, T.; Testa, E.; Beuve, M.
Abstract : The main challenge of radiotherapy is to focus the irradiation dose in cancer cells while preserving the healthy cells surrounding the tumor. Among the different strategies, the use of radiosensitizers aims to amplify the destructive effects of dose in the tumor[1] . Nanoparticles of heavy metals such as gold, are particularly promising radiosensitizers. If their radiosensitizer effect has been studied for about two decades, the origin of this phenomenon is yet quite unknown and barely quantified. Literature suggests that irradiation would generate a physical effect called Auger cascades. This effect would lead to a local increase secondary electrons around the nanoparticle, thus amplifying the critical cell damages of direct sensible molecules such as DNA, or through a boost of free radicals. These effects are produced at nanometric scales and at very short time ( 10 - 15 to 10 - 12 seconds) but have consequences on the patient scale. Because these physical and chemical effects are not directly observable, the simulation tool is therefore mandatory to better understand the initial mechanisms. Our goal is to first develop a simulation that enables us to calculate the spatial dose and free radicals distribution around the nanoparticles, and to quantify the induced boost[2, 3] . To achieve this first step, we developed a low energy Monte Carlo code which can, on nanometric scales, track secondary electrons down to thermalization energy both in water and gold. Solid physics models have been implemented for gold (surface/bulk plasmons), and the code accounts for macroscopic potential differences between two media. Secondly, we want to inject the results in the model NanOx [4], originally developed at IPNL to calculate the biological dose in hadrontherapy. These two allow us to assess the quality of our models, and the relevance of the scenarii offered in literature. The final aim is to guide the development of the nanoparticles and, if possible, to help to planify clinical treatment of nanoparticle-based radiotherapy. We show a dependance of the nanodosimetry in a specific range around nanoparticles according to the energy (20–90 keV) of photons and the nanoparticle size, and the impact in the free radical production compared to pure water.